Strategi Peningkatan Daya Saing Ekspor Indonesia di Pasar Internasional: A Systematic Literature Review - Nilam Gustian (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to identify and analyze strategies for improving Indonesia's export competitiveness in the international market using a Systematic Literature Review (SLR) approach. The main issue addressed is the challenge of Indonesia's export competitiveness, which is influenced by product quality, industrial productivity, innovation, trade policies, digitalization, and global market dynamics. The study employed the SLR method by systematically collecting, screening, and analyzing relevant scholarly articles from reputable academic databases based on predetermined inclusion and exclusion criteria. The findings indicate that enhancing Indonesia's export competitiveness requires integrated strategies, including improving product quality and value-added, adopting digital technologies, strengthening innovation and human resource capabilities, diversifying export markets, optimizing international trade agreements, and improving logistics efficiency and trade governance. Collaboration among the government, business sectors, and supporting institutions plays a crucial role in strengthening Indonesia's competitive position in the global market. The findings provide valuable insights for policymakers and stakeholders in formulating adaptive export strategies to respond effectively to the evolving international trade environment.